Constraint-based configuration of embedded automotive software. (21st December 2010) - Nica, Mihai; Peischl, Bernhard; Wotawa, Franz
Adopting mass customisation approaches allows companies to build a variety of systems with a certain technical diversity. In the automotive industry thousands of variation points and configuration parameters need to be managed for engineering as well as production. Today we are aware of successful applications of configuration techniques in mass-volume production. However, the potential of variability management in engineering embedded automotive systems is recognised rather vaguely. In this paper, we apply configuration techniques for software deployment in the automotive domain. We discuss a simplified problem scenario, outline the used constraint-based model for software deployment, present a prototype implementation, and give first empirical results obtained from the prototype implementation of the constraint model.